Associations Between Asthma Control and Airway Obstruction and Performance of Activities of Daily Living in Older Adults with Asthma. Issue 5 (10th May 2016) - Woods, Eric C.; O'Conor, Rachel; Martynenko, Melissa; Wolf, Michael S.; Wisnivesky, Juan P.; Federman, Alex D.
Abstract : Objectives: To determine the effect of asthma on functional limitations of older adults in the United States. Design: Analyses were conducted with data from the Asthma Beliefs and Literacy in the Elderly study, a prospective cohort study of people aged 60 and older with asthma. Setting: Participants were recruited from urban primary care and pulmonary specialty practices in New York City and Chicago between 2010 and 2012. Participants: Individuals aged 60 and older with asthma (380 women, 72 men, mean age 67.5 ± 6.8 (range 60–98), 40% Latino, 30% black). Measurements: Characteristics of participants with and without activity of daily living (ADL) limitations were compared using the chi‐square test. Generalized estimating equations were used to model the relationships between poor asthma control (Asthma Control Questionnaire (ACQ) score >1.5) and severity of airway obstruction (forced expiratory volume in 1‐second (FEV1 )) and number of ADL limitations. Results: Participants with one or more ADL limitations were more likely to be female (90% vs 81%, P = .02) and Latino (58% vs 32%, P < .001), have less than a high school education (53% vs 27%, P < .001) and an income of 1, 350 per month or less (79% vs 46%, P < .001), and be unmarried (78% vs 64%, P = .003). In the adjusted analysis, poorer ACQ scores (odds ratio (OR) = 1.6, 95% confidence interval (CI) = 1.0–2.4; P = .05) but not severity of airway obstruction (OR = 1.1, 95% CI = 0.6–1.9) was associated with greater ADL limitations. Conclusion: Older adults reporting poor asthma control are more likely to have ADL limitations than those with controlled asthma, although one‐time spirometry may not adequately identify those at risk of physical impairment from asthma.